Digital media tools - Chapman, Nigel (Wiley, 2002)
A practical guide to the industry-leading multi-media authoring tools Creating multimedia presentations requires an understanding of how to manipulate media such as graphics, video, or text, and how to bring them together using a variety of complex software tools. This book offers a clearly focused introduction to the most popular applications used for multimedia authoring, including Photoshop, Premier, and Flash. With an emphasis on multimedia authoring for the Web, the authors provide step-by-step tutorials on how to use these software tools to prepare illustrations, still images, video animation, and sound. Readers will acquire a basic fluency with these tools, discover what they do best and what are their limitations, and learn how they compare with other commonly used software tools.